2018
DOI: 10.1111/1751-7915.13356
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of genome editing tools by bacterial extracellular vesicles

Abstract: Here we propose to use bacterial cells as factories that generate EVs harboring both the RNP complex (or any other CRISPR‐mediated tool) and a specific ligand molecule. The ligand would allow specific binding of EVs to cells with the matching receptors, adding a level of specificity to the delivery, hence stimulating precise genome editing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Available data however suggests a significant impact on the biogeochemical cycles. EVs are potentially involved in cell communication, competition and survival of bacteria (Liu et al, 2019). Interactions between ultramicro-prokaryotes and other micro-organisms communities may shape natural microbiome function (Castelle et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Available data however suggests a significant impact on the biogeochemical cycles. EVs are potentially involved in cell communication, competition and survival of bacteria (Liu et al, 2019). Interactions between ultramicro-prokaryotes and other micro-organisms communities may shape natural microbiome function (Castelle et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EV) in Gram-negative bacteria have been studied for their pathogenicity, host-pathogen interaction and potential targets in vaccine development 31 . Very recently, studies on EV were performed in probiotic strains and revealed potential delivery of bacteriocins and other beneficial properties through the EV 32,33 . Advancing research on EV of probiotics is highly recommended as it will provide further understanding on molecular mechanisms of probiotic bactericidal properties against pathogens and immune modulation.…”
Section: Mechanisms Of Probiotics In Interfering With Pathogens and Imentioning
confidence: 99%
“…Zukünftig sollen Membranvesikel auch für die Genom‐Editierung, also die beliebige Veränderung, das Entfernen oder Einfügen von Genen in Chromosomen, eingesetzt werden . Die zur Zeit effizienteste Methode der Genom‐Editierung beruht auf einem System, das viele Bakterienspezies entwickelt haben, um Fremd‐DNA, die entweder durch Infektion mit Phagen oder über horizontalen Gentransfer in diese eindringt, zu erkennen und abzubauen (Abbildung ).…”
Section: Membranvesikel Und Gen‐editierungunclassified